The Effect of Work Family Conflict on Job Performance: Emotional Intelligence and Job Satisfaction as Mediating Variables - Sheilla Syiam Rahmawati; Justine Tanuwijaya; Norzanah Mat Nor (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyse the effect of work-family conflict on job performance with emotional intelligence and job satisfaction as mediating variables in 3 and 4-star hotel employees in Jakarta. The research was conducted with a quantitative approach.The determination of the sample was carried out using nonprobability sampling with the purposive sampling method, and refers to the minimum sample size according to Hair et al. (2019). The sample in this study amounted to 265 employees of 3 and 4-star hotels in Jakarta. The data analysis technique used is the Structural Equation Model (SEM) method. The technique of data collection used is by distributing questionnaires through the Google Form application. The results of hypothesis testing show that the seven hypotheses proposed are supported by the statement that there is an effect of work-family conflict on job performance, with emotional intelligence and job satisfaction as mediating variables.